Lifestyle Changes Related to Eating Habits, Physical Activity, and Weight Status During COVID-19 Quarantine in Italy and Some European Countries - Catucci, Arianna; Scognamiglio, Umberto; Rossi, Laura (Frontiers in Nutrition, 2021)
The novel human coronavirus disease (COVID-19) is an infectious respiratory disease that has affected more than 50 million people all over the world up to November 2020, becoming the fifth documented pandemic since the Spanish flu pandemic which broke out in 1918. Since SARS-CoV-2 appeared in China, the virus evolved for four months within the country and spread to other countries around the world as a global threat. There is currently no drug approved by the Food and Drug Administration (FDA) for which efficacy on the virus has been proved. Therefore, the only strategy that can be followed against this virus is the use of measures that are capable of reducing its spread such as isolation and quarantine, social distancing, community-wide containment and the implementation of a strict regime of hygiene rules. Quarantine has proved to be a valuable means of combating the spread of the virus; however, it has inevitably led to a radical change in people’s life. With the aim of highlighting the role that quarantine has played in determining lifestyle changes both in eating habits and in physical activity and its possible correlation with weight increase, studies conducted in Italy and some European countries have been selected. The selection criterion was the type of questionnaire which had to include information on the weight status and at least one of the other two aspects: lifestyle changes in eating habits and/or physical activity during the quarantine period. The results obtained indicate, in general, a negative effect of quarantine on eating habits and physical activity as there has been an increase in food consumption and a reduction in physical activity with a consequent increase in weight.